2021
DOI: 10.1186/s12888-021-03507-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy and quality of life in Iran: a cross-sectional study

Abstract: Background Mental health is one of the effective factors in the quality of life of people. The aim of the present study was to determine the status of mental health literacy (MHL) and its relationship with the quality of life across the Iranian general population. Methods In this cross-sectional study, a multi-stage sampling method was used to survey 1070 participants from the city of Gonabad (Iran). The data collection tools were demographics sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
3
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 52 publications
(77 reference statements)
3
30
3
6
Order By: Relevance
“…It is likely that students who are equipped with information about mental health, and who seek help regarding mental health have a significantly higher quality of life. This conclusion is consistent with a study of Jafari et al (2021), who found that mental health literacy enhances QoL. Similarly, Ran et al (2018) found a significant relationship between health literacy and quality of life.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is likely that students who are equipped with information about mental health, and who seek help regarding mental health have a significantly higher quality of life. This conclusion is consistent with a study of Jafari et al (2021), who found that mental health literacy enhances QoL. Similarly, Ran et al (2018) found a significant relationship between health literacy and quality of life.…”
Section: Discussionsupporting
confidence: 91%
“…The quality of life is reflected in the dimensions of physical and mental health as influenced by various economic, social, mental, and physical factors (Goodyear et al, 2021;Jafari et al, 2021). Observance of mental health literacy (MHL) is one of the most important strategies to reducing mental health disorders (Renwick et al, 2022).…”
Section: Mental Health Literacy and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review found a positive effect of school-based educational interventions on improving mental health literacy (MHL) in adolescents ( Olyani et al, 2021 ). The evidence has also underlined the need to promote MHL throughout the life span and in different contexts ( Morgado et al, 2021b ), because it increases the quality of life of people ( Jafari et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Internal consistency, test-retest reliability, and construct validity have been demonstrated. Since the MHLS was developed in 2015, it has been used to measure MHL in various countries, and the MHLS has also been reported to be positively correlated with help-seeking (General Help-Seeking Questionnaire; GHSQ) 18) and quality of life (SF-12) 19) . Furthermore, the MHLS has been translated into Vietnamese 20) , Persian 21) , Arabic 22) , and Chinese 23) .…”
Section: Introductionmentioning
confidence: 99%